Goodwin cycles and the BoPC growth paradigm: A macrodynamic model of growth and fluctuations - Marwil J. Dávila-Fernández; Gilberto A. Libânio (EconomiA, 2016)
The paper builds a non-linear macrodynamic model to study the relation between the functional distribution of income, technological progress and economic growth. In the short-term, the interaction between the productivity regime, the demand regime and the distributive conflict generates cyclical paths a la Goodwin. In the long-term, output growth rate is constrained by the balance of payments a la Thirlwall, in which the elasticities of foreign trade are modeled as a function of the complex relation between the wage-share and the innovation capabilities of theeconomy. – – O artigo constrói um modelo dinâmico n\~ao-linear para estudar a relaç\~ao entre a distribuiç\~ao funcional da renda, o progresso técnico e o crescimento econômico. No curto prazo, a interaç\~ao entre o regime de produtividade, o regime de demanda e o conflito distributivo gera trajetórias cíclicas a la Goodwin. No longo prazo, o crescimento do produto é restrito pelo balanço de pagamentos a la Thirlwall, em que as elasticidades de comércio exterior s\~ao modeladas pela complexa relaç\~ao entre o wage-share e a capacidade inovativa da economia.
Keywords: E12; E32; O11; 330; Cyclical growth; Goodwin cycles; Distributive cycles; Thirlwall's law; Balance of payments constraint